IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM MEMOTIVASI SISWA BERWIRAUSAHA DENGAN PEMBELAJARAN BERBASIS PROYEK KELAS IV A DI SDN 003 LOA JANAN ILIR TAHUN AJAR 2024/2025 - Tori, Angela Apriliana; Adianto, Samsul (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2024)
The purpose of this study was to determine the Implementation of the Independent Learning Curriculum in Motivating Students with Project-Based Learning in Class IV A SDN 003 Loa Janan Ilir. This study uses a descriptive qualitative method. From the results of the research conducted, the implementation of the independent learning curriculum in motivating students to become entrepreneurs with project-based learning went well, students were very enthusiastic about participating in learning and students were motivated to become entrepreneurs.The Entrepreneurship Project carried out was making key chains from clay, this project was carried out for approximately one month from the planning stage to the marketing stage. The advantages of the project of making key chains from clay can motivate students to become entrepreneurs, this project was chosen because the cost is affordable among elementary school students and the manufacturing process is easy to implement by elementary school students, the disadvantages of this project are at the time of project implementation, and the lack of suggestions and infrastructure from the school. In addition to making key chains from clay, there are many entrepreneurial projects that can be done by elementary school students, for example, recycling plastic waste into valuable items, making toys from used goods, and many more.